An Act to Incorporate and Establish the City of Dubuque, 1845 Iowa Laws 119, chap 123, § 12 - (:unkn) unknown (General Publisher, 1845)
Authorized the town of Dubuque to regulate the storage and sale of gunpowder.
--
Keywords: GUN POWDER STORAGE